Pengembangan Media Pembelajaran Interaktif dengan Pendekatan Contextual Teaching and Learning - Septiani, Norma; Asih, Endang Cahya Mulyaning (Department of Mathematics Education Program IPI Garut, 2024)
Penelitian ini merupakan pengembangan media pembelajaran matematika interaktif berupa aplikasi yang dapat dijalankan di smartphone dengan pendekatan Contextual Teaching and Learning (CTL). Tujuan dari penelitian ini adalah Mengembangkan media pembelajaran matematika interaktif dengan pendekatan Contextual Teaching and Learning (CTL) yang layak digunakan siswa SMP; Melihat respon siswa terhadap media pembelajaran yang dikembangkan; dan Melihat keefektifan media pembelajaran yang dikembangkan. Metode penelitian ini adalah Research and Development (R&D) dengan tahapan pengembangan ADDIE yaitu tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Media pembelajaran yang dikembangkan dalam penelitian ini berupa aplikasi yang bernama Math Of Algebra (MOA) yang diujicobakan kepada 34 siswa SMP. Aplikasi Math of Algebra (MOA) dapat dijalankan di smartphone android yang berisi ringkasan materi, contoh soal, latihan soal dan kuis materi aljabar untuk siswa kelas VII SMP. Hasil penilaian ahli materi mendapat skor rata-rata 4,3 dengan kategori sangat valid sedangkan hasil penilaian ahli media mendapatkan skor rata-rata 4,2 dengan kategori valid. Hasil respon siswa mendapatkan skor rata-rata 4,4 dan termasuk pada kategori sangat baik. Keefektifan media dilihat dari persentase hasil ketuntasan belajar dan pada penelitian ini sebesar 72,2% dengan kategori efektif. Hasil tersebut menunjukkan bahwa aplikasi Math of Algebra (MoA) berkualitas. This research is the development of interactive mathematics learning media in the form of an application that can be run on a smartphone with a Contextual Teaching and Learning (CTL) approach. The objectives of this study are To develop interactive mathematics learning media with a Contextual Teaching and Learning (CTL) approach that is suitable for use by junior high school students; To see students' responses to the developed learning media; and To see the effectiveness of the developed learning media. This research method is Research and Development (R&D) with ADDIE development stages, namely the analysis, design, development, implementation, and evaluation stages. The learning media developed in this study is an application called Math Of Algebra (MOA) which was tested on 34 junior high school students. The Math of Algebra (MOA) application can be run on an Android smartphone that contains a summary of the material, sample questions, practice questions, and quizzes on algebra material for grade VII junior high school students. The results of the material expert assessment got an average score of 4.3 with a very valid category while the results of the media expert assessment got an average score of 4.2 with a valid category. The results of the student responses got an average score of 4.4 and were included in the very good category. The effectiveness of the media is seen from the percentage of learning completion results and in this study, it was 72.2% with an effective category. These results indicate that the Math of Algebra (MoA) application is of high quality.